The direct and indirect effect of interest rates on economic growth in Botswana - Masole, Mbako (My University, 2021)
The study determines the direct and indirect effects of interest rates on economic growth through domestic investment, real exchange rate, inflation, foreign direct investment (FDI), trade openness and human capital. The results of this study will guide the appropriate intervention in the use of interest rates in stimulating economic growth. The study uses a quantitative method with multiple regression analysis. It examines the effects of interest rates on economic growth and domestic investment, FDI, inflation, real effective exchange rate and trade openness from 2004 to 2019 in Botswana. The study is highly reliant on secondary data, and quarterly data is used to run the regressions. The results show that the real interest rate in Botswana has a negative effect on domestic investment and inflation, with domestic investment being statistically significant and inflation not statistically significant. However, it has a positive effect on real exchange rate, FDI and trade openness. FDI and real exchange rate is statistically significant whereas trade openness is stastically insignificant. Real exchange rate and trade openness have a positive effect on economic growth, while domestic investment, inflation, real interest rate and FDI have a negative effect on economic growth. Domestic investment is statistically significant, while real exchange rate, inflation, FDI and trade openness are statistically insignificant. On the path analysis, exchange rate, inflation, FDI and trade openness cannot mediate the effect of interest rates on economic growth, whereas domestic investment mediates the effect of interest rate on economic growth. The study concludes that it is critical for policy makers, when making policy decisions on the monetary policy, to bear in mind the influence of interest rate on other macro-economic factors, and how these subsquently affect economic growth. The use of interest rate did not yield the desired results in Botswana, it is therefore rather recommended to consider the use of fiscal policy to stimulate economic growth.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Management (in Finance and Investment), 2021
Keywords: Interest Rates; Economic Growth; Botswana; Domestic investment; Real exchange rate; Inflation; SDG-8: Decent work and economic growth